The Effectiveness of Warm Water Soak Therapy on Feet and Classical Music Therapy on Blood Pressure of Hypertensive Clients at Puskesmas Ijen Bondowoso - Rahman, Handono Fatkhur; Bahri, Saipul; Siswanto, Heri (Universitas Islam Lamongan, 2020)
Hypertension is one of the diseases that attack on the cardiovascular system. Management to overcome hypertension can use pharmacological therapy and nonpharmacological therapy. Non-pharmacological therapies for hypertension include soaking warm water on the feet and classical music therapy. This study aims to determine the effectiveness of warm water soak therapy in the feet and classical music therapy on hypertension client blood pressure. The research design used in this research is using Pre Post experimental design. Sampling techniques use simple ramdom sampling. The number of respondents in this study were 20 respondents for warm water bath therapy and 20 respondents for classical music therapy. The results of this study indicate that in systolic blood pressure there is a difference in the effectiveness of warm water soak therapy in the feet and classical music therapy with p value (0.036) <Î± (0.05) while diastole blood pressure does not differ in the effectiveness of warm water soak therapy in foot and classical music therapy with p-value diastole (0.108)> Î± (0.05). Based on the mean value, it is known that warm water soak therapy on the foot has a mean systole value (150 mmhg) and mean diastole value (89.67 mmhg), while the mean value of sistole in classical music therapy (154.5 mmhg) and the mean diastole value of classical music therapy ( 92 mmhg) so that from the mean results the soak therapy in warm water on the feet is more effective in reducing blood pressure.